Analysis of Job Value-Based Compensation System At Automotive Company XYZ In Bali Province - Sintya Ismana Gardenia Tanaya; Muhammad Naufal; Miranda Anastasya Veronica; Ehug Togi; Siti Tasya Octa Aeni (Ridwan Institute, 2021)
Compensation is a form of reward from an organization for the performance of its members. There are 2 types of compensation, namely financial and non-financial compensation. Compensation, especially the financial type, will affect the welfare of the recipient. This study will discuss the improvement of compensation in accordance with the method point system with company policy. The studied company is a company that is engaged in the automotive field that focuses on used-vehicle transactions, sale of spare parts, and vehicle services. The purpose of this research is (1) to develop job grading and job values for employees of company XYZ based on compensable factors according to scientific journals (2) to evaluate compensation system improvements that are appropriate and effective to be imp lemented in company XYZ. The data in this study are quantitative, primary data obtained through direct interviews and the results of questionnaires and secondary data obtained through literature studies and relevant reports. The method used is salary mapping adhered, and salary mapping overlapping. The result of the research shows that there are 10 compensable factors that become the job evaluation factors that form the basis for compensation. All factors are divided into 3 parts according to Hay's method, namely know-how, problem solving, and accountability. The results of the salary reform design that have been obtained can be used as the company's new payroll system